2021
DOI: 10.1371/journal.pone.0254833
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the healthiness of UK food companies’ product portfolios using food sales and nutrient composition data

Abstract: Background The provision and over-consumption of foods high in energy, saturated fat, free sugars or salt are important risk factors for poor diet and ill-health. In the UK, policies seek to drive improvement through voluntary reformulation of single nutrients in key food groups. There has been little consideration of the overall progress by individual companies. This study assesses recent changes in the nutrient profile of brands and products sold by the top 10 food and beverage companies in the UK. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Underlying the importance of strengthening the commitments lies the assumption that stronger commitments will translate into improved practices and performance. Similar to earlier research however, this study found no relationship between voluntary commitments and healthier product portfolios [ 16 , 42 ]. More importantly, earlier research pointed towards the importance of being cautious with voluntary company commitments as these might help to legitimize and advertise the food industry’s role in improving population health without any assurance that company practices go beyond business as usual [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…Underlying the importance of strengthening the commitments lies the assumption that stronger commitments will translate into improved practices and performance. Similar to earlier research however, this study found no relationship between voluntary commitments and healthier product portfolios [ 16 , 42 ]. More importantly, earlier research pointed towards the importance of being cautious with voluntary company commitments as these might help to legitimize and advertise the food industry’s role in improving population health without any assurance that company practices go beyond business as usual [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…It is expected that strengthened commitments will translate into improved practices and performance. Nevertheless, this needs to be closely monitored as research in the UK has shown that voluntary reformulation policies between 2015 and 2018 did not translate into noteworthy changes in the nutritional quality of products sold by the top ten food and beverage manufacturers [36]. Also in Canada it was found that companies with stronger commitments within the area of product reformulation did not have portfolios with a better nutritional quality [37].…”
Section: Discussionmentioning
confidence: 99%
“…Similar analyses have been done for the product portfolios of the major UK food companies, and they show that over the last 4 years, there has been very little improvement in the overall portfolio of any of the companies listed (Bandy et al, 2021). This is despite these companies telling us about all their healthy options.…”
Section: Figurementioning
confidence: 69%